2013
DOI: 10.1016/j.ijpp.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Do diseases cause entheseal changes at fibrous entheses?

Abstract: Fibrous entheses have been widely used to study activity-related stress to infer behavioural patterns in past populations. Unlike their fibrocartilaginous counterparts, the effect of disease processes has been less widely discussed in the osteoarchaeological literature. This study uses a literature review to ascertain whether specific pathological changes should be taken into account when recording fibrous entheses. Due to the anatomical structure of fibrous entheses it was hypothesised that diseases which aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 66 publications
0
10
0
2
Order By: Relevance
“…Although the focus of this study is the estimation of differences in physical activity between the sexes in the past, one needs to first take into account the multifactorial etiology of ECs. Besides biomechanical factors, other relevant variables include age, body size, pathological conditions, hormonal and probably genetic factors (Henderson, 2013; Henderson & Nikita, 2016; Jurmain, Cardoso, Henderson, & Villotte, 2012; Milella et al, 2012; Weiss, Corona, & Schultz, 2012; Wilczak, 1998). The effect of hormonal and genetic factors on ECs in our sample cannot be tested at the moment and their influence on our results accordingly needs to be kept as a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Although the focus of this study is the estimation of differences in physical activity between the sexes in the past, one needs to first take into account the multifactorial etiology of ECs. Besides biomechanical factors, other relevant variables include age, body size, pathological conditions, hormonal and probably genetic factors (Henderson, 2013; Henderson & Nikita, 2016; Jurmain, Cardoso, Henderson, & Villotte, 2012; Milella et al, 2012; Weiss, Corona, & Schultz, 2012; Wilczak, 1998). The effect of hormonal and genetic factors on ECs in our sample cannot be tested at the moment and their influence on our results accordingly needs to be kept as a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Further, these regions are part of an "enthesis organ complex," dissipating stress at the bony interface away from the attachment site. Hence, abnormal changes (e.g., diffuse idiopathic skeletal hyperostosis (DISH), synovitis, bursitis) may also result as part of the complex system of soft and hard tissues within the enthesis organ complex (Benjamin et al, 2002(Benjamin et al, , 2006Henderson, 2013;Schrader, 2019).…”
Section: Entheseal Changesmentioning
confidence: 99%
“…This lack of direct association between activity and ECs has been attributed to the fact that a combination of factors, such as age, body mass, sex, metabolism, genetic predisposition and certain pathological conditions, also contribute to EC development (e.g. Benjamin & McGonagle, 2001;Henderson, 2008Henderson, , 2013Jurmain et al, 2011;Niinimäki, 2011;Milella et al, 2012;Weiss et al, 2012). Indeed, several studies have found that age is the primary factor affecting ECs with older individuals generally exhibiting more pronounced changes (e.g.…”
Section: Introductionmentioning
confidence: 99%